2017
DOI: 10.3389/fnins.2017.00095
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological and Behavioral Responses of Mandarin Lexical Tone Processing

Abstract: Language experience enhances discrimination of speech contrasts at a behavioral- perceptual level, as well as at a pre-attentive level, as indexed by event-related potential (ERP) mismatch negativity (MMN) responses. The enhanced sensitivity could be the result of changes in acoustic resolution and/or long-term memory representations of the relevant information in the auditory cortex. To examine these possibilities, we used a short (ca. 600 ms) vs. long (ca. 2,600 ms) interstimulus interval (ISI) in a passive,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 95 publications
0
40
2
Order By: Relevance
“…As predicted, English listeners showed the poorest discrimination and identification for the vowel contrast /y/ vs. /u/, and poorer performance in the long ISI condition. In contrast to Yu et al (2017) , however, we found no effect of ISI reflected in the neural responses, specifically the mismatch negativity (MMN), P3a and late negativity ERP amplitudes. We did see a language group effect, with Mandarin listeners generally showing larger MMN and English listeners showing larger P3a.…”
contrasting
confidence: 95%
See 3 more Smart Citations
“…As predicted, English listeners showed the poorest discrimination and identification for the vowel contrast /y/ vs. /u/, and poorer performance in the long ISI condition. In contrast to Yu et al (2017) , however, we found no effect of ISI reflected in the neural responses, specifically the mismatch negativity (MMN), P3a and late negativity ERP amplitudes. We did see a language group effect, with Mandarin listeners generally showing larger MMN and English listeners showing larger P3a.…”
contrasting
confidence: 95%
“…The MMN amplitude was greatly reduced in high repeaters under the long ISI condition compared to that of the short ISI condition, and no MMN was observed for either the short or long ISI conditions in the low repeaters. In Yu et al (2017) , we found that native speakers of English failed to show an early negativity (i.e., MMN) to a Mandarin lexical tone contrast, which is phonemic in Mandarin but not English, when the ISI was greater than 2.5 s; however, English listeners did show MMN to the lexical tone contrast under a short ISI of approximately 500 ms. The Mandarin native listeners showed comparable MMNs for both the long and short ISI.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…In order to explore the processing of acoustic and phonological information in lexical tones, previous studies have adopted several methods to distinguish the acoustic information from the phonological information in lexical tones, such as the cross-language (native vs. nonnative) comparison (e.g., Chandrasekaran, Krishnan, & Gandour, 2007), speech and nonspeech (hum) comparison (e.g., Jia, Tsang, Huang, & Chen, 2015), interstimulus interval manipulation (Y. H. Yu, Shafer, & Sussman, 2017), and categorical perception paradigm (e.g., Xi et al, 2010).…”
Section: Dissociation Of Acoustic Information and Phonological Infomentioning
confidence: 99%